KELAYAKAN MEDIA VIDEO YOUTUBE KIDS PADA SEKOLAH DASAR - Zainul Abidin (JUPI (Jurnal Pendidikan Indonesia), 2023)
This development research aims to produce media in the form of learning videos of human and environmental materials with a process through a feasibility test process so that it can be used for learning. This research uses the ADDIE development model with 5 stages, including needs analysis, design, development, media application and evaluation. The subject users in this development are grade III students of SD Negeri 2 Tulangan. This type of research uses qualitative research in the form of giving questionnaires to experts and testing students. Based on the results of research that this learning video is valid and feasible to use for learning. So it can be concluded that learning videos on YouTube Kids can be used as learning media in elementary school education units.